Lean Healthcare in the institutional, professional, and patient perspective: an integrative review - Hellen Maria de Lima Graf Fernandes; Mariana Véo Nery de Jesus; Dirceu da Silva; Edinêis de Brito Guirardello (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the scientific evidences in the literature about the evaluation of Lean Healthcare after its implementation. Method: An integrative review conducted in the CINAHL, Scopus, WOS, and Embase databases, and in the PubMed portal, resulting in 18 articles published in English, Spanish and Portuguese, from 2008 to 2019. Results: The findings were categorized into results for the institution, professional, and patient. The predominant category was institutional, with cost analysis and increased productivity, followed by the professional, with job satisfaction and leadership, and finally the patient, with satisfaction, attitudes, and behaviors. Conclusion: This study reinforces the need to establish, for management, a systematic method of monitoring the results achieved in the Lean Healthcare implementation phase. Since the value in this method is defined by the patient, further research in this aspect may lead to new evidence.